2015
DOI: 10.1108/bfj-06-2014-0193
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the purchasing behaviour of Taiwanese meat consumers in light of rising sustainability concerns

Abstract: Purpose -The purpose of this paper is to provide an exploratory study of how Taiwanese consumer concerns about sustainability issues relating to pork are linked to their purchasing behaviours, using the case of "warm" meat. Design/methodology/approach -The study is based on qualitative semi-structured interviews of a cluster random sample of meat-purchasing consumers in Taiwan. The study data are analysed in light of grounded theory, to provide a clearer understanding of interviewees' sustainability concerns a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…As such, our findings concur with Erdem et al (2010), who claimed that education can influence how consumers value sustainability as a factor for eating animal protein. We can also note that our results are consistent with findings of Jen and Wang (2015) and Clonan et al (2015), but not related to animal welfare per se .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…As such, our findings concur with Erdem et al (2010), who claimed that education can influence how consumers value sustainability as a factor for eating animal protein. We can also note that our results are consistent with findings of Jen and Wang (2015) and Clonan et al (2015), but not related to animal welfare per se .…”
Section: Resultssupporting
confidence: 91%
“…The fact that gender and age have no bearing on perceptual changes due to higher prices of beef products was surprising. Many studies have suggested that younger consumers are more inclined to consider altruistic characteristics as critical to their lifestyle (Gaitán-Cremaschi et al , 2015; Jen and Wang, 2015; Clonan et al , 2015). However, higher prices have compelled 37.9 percent of our sample to reduce or stop beef consumption altogether.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…too much information at the same time) should be avoided, because it may lead to consumer inertia and fatigue [51]. Also, communication in supermarkets is usually more impersonal, with consumers informing themselves by reading labels or by looking at advertising, while in traditional markets, as it is the case for bodegas, communication is more personal and direct between customers and the owner [52]. This is relevant because door-to-door promotions and face-to-face communications have found to be effective techniques to influence people's attitudes towards recycling [34].…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…Trust is a key factor that influences purchase behavior relating to foods [ 18 , 19 ], especially certified traceable foods [ 20 ]. Furthermore, institutional trust is the standard predictor of trust in major institutions in a ganizations [ 21 ], such as governments and legal organizations [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%